Evaluation of Biotechnological Active Peptides Secreted by Saccharomyces cerevisiae with Potential Skin Benefits - Elisabete Muchagato Maurício; Patrícia Branco; Ana Luiza Barros Araújo; Catarina Roma-Rodrigues; Katelene Lima; Maria Paula Duarte; Alexandra R. Fernandes; Helena Albergaria (MDPI AG, 2024)
Biotechnological active peptides are gaining interest in the cosmetics industry due to their antimicrobial, anti-inflammatory, antioxidant, and anti-collagenase (ACE) effects, as well as wound healing properties, making them suitable for cosmetic formulations. The antimicrobial activity of peptides (2-10 kDa) secreted by Saccharomyces cerevisiae Ethanol-Red was evaluated against dermal pathogens using broth microdilution and challenge tests. ACE was assessed using a collagenase activity colorimetric assay, antioxidant activity via spectrophotometric monitoring of nitrotetrazolium blue chloride (NBT) reduction, and anti-inflammatory effects by quantifying TNF-α mRNA in lipopolysaccharides (LPS)-exposed dermal fibroblasts. Wound healing assays involved human fibroblasts, endothelial cells, and dermal keratinocytes. The peptides (2-10 kDa) exhibited antimicrobial activity against 10 dermal pathogens, with the Minimum Inhibitory Concentrations (MICs) ranging from 125 µg/mL for Staphylococcus aureus to 1000 µg/mL for Candida albicans and Streptococcus pyogenes. In the challenge test, peptides at their MICs reduced microbial counts significantly, fulfilling ISO 11930:2019 standards, except against Aspergillus brasiliensis. The peptides combined with MicrocareⓇ SB showed synergy, particularly against C. albicans and A. brasilensis. In vitro, the peptides inhibited collagenase activity by 41.8% and 94.5% at 250 and 1000 µg/mL, respectively, and demonstrated antioxidant capacity. Pre-incubation with peptides decreased TNF-α expression in fibroblasts, indicating anti-inflammatory effects. The peptides do not show to promote or inhibit the angiogenesis of endothelial cells, but are able to attenuate fibrosis, scar formation, and chronic inflammation during the final phases of the wound healing process. The peptides showed antimicrobial, antioxidant, ACE, and anti-inflammatory properties, highlighting their potential as multifunctional bioactive ingredients in skincare, warranting further optimization and exploration in cosmetic applications.